BILATERAL GENU VALGUM AS AN UNSUAL PRESENTATION OF PRIMARY HYPERPARATHYROIDISM - L, Siow Ping; L, Leh Teng; MA, Norhaliza (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Primary hyperparathyroidism (PHPT) is a disorder of bone and mineral metabolism caused by autonomous secretion of parathyroid hormone (PTH). The most common cause is parathyroid adenoma, followed by parathyroid hyperplasia and rarely parathyroid carcinoma. Parathyroid adenoma can occur sporadically or as part of multiple endocrine neoplasia (MEN) type 1 or type 2A. Sporadic PHPT in adolescents is uncommon and is often associated with severe symptomatic end organ damage compared to adults. The skeletal manifestations include bone pain and fractures. Limb deformity is an atypical and rare presentation. We report a young patient with bilateral knock knee who was subsequently diagnosed to have a parathyroid adenoma. CASE A 15-year-old Malay boy presented with bilateral knock knee of six months’ duration. He had no history of recurrent fractures, bone pain, abdominal pain, vomiting or constipation. There was no family history of renal calculi or MEN related disorders. Physical examination showed bilateral genu valgum deformity with short stature. He had elevated levels of serum calcium (3 mmol/L), alkaline phosphatase (1258 U/L) and intact PTH (154 pmol/L). His serum phosphate level was 0.8 mmol/L with normal renal function. Ultrasonography of the neck showed a left inferior parathyroid adenoma. Following parathyroidectomy, histopathologic examination was consistent with parathyroid adenoma. His serum calcium 2 months after surgery returned to normal (2.14 mmol/L). Genu valgum has been described as one of the skeletal manifestations of primary hyperparathyroidism in adolescents. The exact mechanism is still not understood. It can be hypothesised that elevated parathyroid hormone levels may have direct effect on the growth plates and bone remodelling during pubertal growth spurt, resulting in genu valgum. In a young patient with parathyroid adenoma, MEN-related disorders should be considered. Parathyroidectomy is the mainstay of treatment in adolescents. CONCLUSION Primary hyperparathyroidism in adolescents can present with isolated genu valgum deformity.